Environmental bacteria increase population growth of hydra at low temperature - Miklós, Máté; Cseri, Karolina; Laczkó, Levente; Kardos, Gábor; Fraune, Sebastian; Tökölyi, Jácint (Frontiers in Microbiology, 2023)
Multicellular organisms engage in complex ecological interactions with microorganisms, some of which are harmful to the host's health and fitness (e.g. pathogens or toxin-producing environmental microbiota), while others are either beneficial or have a neutral impact (as seen in components of host-associated microbiota). Although environmental microorganisms are generally considered to have no significant impact on animal fitness, there is evidence suggesting that exposure to these microbes might be required for proper immune maturation and research in vertebrates has shown that developing in a sterile environment detrimentally impacts health later in life. However, it remains uncertain whether such beneficial effects of environmental microorganisms are present in invertebrates that lack an adaptive immune system. In the present study, we conducted an experiment with field-collected Hydra oligactis, a cold-adapted freshwater cnidarian. We cultured these organisms in normal and autoclaved lake water at two distinct temperatures: 8 °C and 12 °C. Our findings indicated that polyps maintained in sterilized lake water displayed reduced population growth that depended on temperature, such that the effect was only present on 8 °C. To better understand the dynamics of microbial communities both inhabiting polyps and their surrounding environment we conducted 16S sequencing before and after treatment, analyzing samples from both the polyps and the water. As a result of culturing in autoclaved lake water, the polyps showed a slightly altered microbiota composition, with some microbial lineages showing significant reduction in abundance, while only a few displayed increased abundances. The autoclaved lake water was recolonized, likely from the surface of hydra polyps, by a complex albeit different community of bacteria, some of which (such as Pseudomonas, Flavobacteriaceae) might be pathogenic to hydra. The abundance of the intracellular symbiont Polynucleobacter was positively related to hydra population size. These findings indicate that at low temperature environmental microbiota can enhance population growth rate in hydra, suggesting that environmental microorganisms can provide benefits to animals even in the absence of an adaptive immune system.